Nanodiamond Theranostic for Light-Controlled Intracellular Heating and Nanoscale Temperature Sensing - Wu, Yingke (Nano Lett, 2021)
[Image: see text] Temperature is an essential parameter in all biological systems, but information about the actual temperature in living cells is limited. Especially, in photothermal therapy, local intracellular temperature changes induce cell death but the local temperature gradients are not known. Highly sensitive nanothermometers would be required to measure and report local temperature changes independent of the intracellular environment, including pH or ions. Fluorescent nanodiamonds (ND) enable temperature sensing at the nanoscale independent of external conditions. Herein, we prepare ND nanothermometers coated with a nanogel shell and the photothermal agent indocyanine green serves as a heat generator and sensor. Upon irradiation, programmed cell death was induced in cancer cells with high spatial control. In parallel, the increase in local temperature was recorded by the ND nanothermometers. This approach represents a great step forward to record local temperature changes in different cellular environments inside cells and correlate these with thermal biology.